Islamic Lifestyle on Hijab Alila YouTube Shows (Episode Bts the Series): Islamic Lifestyle Pada Tayangan YouTube Hijab Aila (Episode Bts The Series) - Fitri Nur Romadhan; Kukuh Sinduwiatmo (Jurnal Spektrum Komunikasi, 2023)
The development of information technology, closely related to globalization, is evident in the significant enthusiasm of the public towards K-Pop and the fading of culture, as exemplified in the content showcased in the web series "Hijab Alila" on YouTube. This research aims to discuss the aspect of signs using Ferdinand de Saussure's theory. In each scene, an analysis of the web series "Between Two Sides: BTS The Series" will be conducted based on the system of signs in Structural Semiotics. Based on the analysis, it is simultaneously developed with the interpretation of the aspects and scenes analyzed as a whole. The researcher adopts a constructivist paradigm with a qualitative approach, providing an insight into the constructed reality of Islamic lifestyle.